IMPLEMENTASI SISTEM JENJANG KARIR DALAM PELAKSANAAN DISCHARGE PLANNING - Wiwin Sulistya Wati (Journal of Nursing Science Update (JNSU), 2016)
Discharge planning can reduce patient readmission. This study aimed to identify relationship of implementation nursing  career ladder system and management function    to the implementation of discharge planning. Design research was descriptive correlation with cross sectional approach. Data were collected through primary data as much as 121 nurses and also secondary data from patient medical records related to discharge planning documentation. The sampling technique was simple random sampling and proportional sampling. Data were analyzed by spearman correlation. The result showed a significant correlation between implementation of career ladder system (p=0,001),  competency assessment (p=0,001), clinical privileges (p=0,001), continuing professional development (p=0,001) and  management function (p=0,001) and  the implementation of discharge planning. It is recommended to the need for discharge planning training for nurse to improve the competency of nurses in implementing discharge planning. Key words: career ladder system, discharge planning, nurses, competency.